General local cohomology modules in view of low points and high points - Sadeghi, M. Y.; Ahmadi Amoli, Kh.; Chaghamirza, М. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5Let $R$ be a commutative Noetherian ring, let $Φ $ be a system of ideals of $R,$ let $M$ be a finitely generated $R$-module, and let $t$ be a nonnegative integer. We first show that a general local cohomology module $H_{Φ}^{i}(M)$ is a finitely generated $R$-module for all $i